Comparison of Effect of Yoga versus Aerobic Exercise on Waist Circumference, Waist-Hip Ratio and Body Mass Index in Overweight and Obese Adult Individuals - Khan, S.; Agrawal, R.; Memon, S. (Kathmandu University Medical Journal, 2022)
Background Obesity is becoming serious global public health issue due to sedentary lifestyle and bad eating habits. Dietary and lifestyle practices are directly related to obesity, which can cause serious health problems like cardiac ailments, diabetes, and hypertension etc. Vast varieties of options are available for weight reduction including physical exercises, various diet plans and also the pharmacological agents. Physical activity improves the fitness of the individual and helps in reducing the ill effects of the obesity. Objective To compare the effects of Yoga and Aerobic Exercise on weight circumference, waist-hip ratio (WHR) and body mass index (BMI) in overweight and obese individuals. Method An experimental study was started with purposive sampling. Sixty overweight and obese individuals from the community were divided equally into two groups, one group was given supervised yoga asana and the other group was given supervised aerobic exercise for 6 weeks. Waist circumference, waist hip ratio and body mass index were taken pre and post intervention. Result Statistically significant difference was seen in pre and post intervention value of waist circumference, waist hip ratio and body mass index in both the groups with the p value < 0.05. However there was no statistical significant difference noted in waist hip ratio in individuals performing aerobic exercises as p value was > 0.05. Conclusion Both the interventions showed significant reduction in waist circumference, waist hip ratio and body mass index, while better results were noted in the individuals performing yoga asanas.